Remote monitoring of patients with axial spondyloarthritis during the COVID-19 pandemic: results and prospects of using the information technology “Aspine” - D. G. Rumiantceva; A. M. Lila; Sh. Erdes (Научно-практическая ревматология, 2021)
During the pandemic of the new coronavirus infection COVID-19, the need for remote communication between doctors and patients has increased around the world.Objective: remote interaction between rheumatologist and patients using “ASpine” technology in the context of the COVID-19 pandemic.Subjects and methods. Within the framework of the scientific project, the information technology “ASpine” was used, which consists of two parts. The first is directly a mobile application for patients with a diagnosis of axial spondyloarthritis and the second is a program for a personal computer that is used by a rheumatologist.In the “ASpine” application, patients fill out BASDAI, ASDAS-CRP, BASFI questionnaires, enter data from various studies, and control the performance of daily exercise therapy. Also, the program has the ability to contact the attending physician via text messages.The paper presents the experience of one rheumatologist with the information technology “ASpine” during the COVID-19 pandemic from April to June 2020.Results. From January 1 to June 6, 2020, the total number of downloads of “ASpine” applications from the AppStore and GooglePlay was 1778, most of all during the COVID-19 pandemic. During this period, a rheumatologist using “ASpine” remotely observed 71 patients with axial spondyloarthritis. 47 (66.1%) of them were attached from April to June 2020. As of June 1, 2020, the average BASDAI in the observed values of patients was 4.7±2.3, BASFI -3.5±2.7, ASDAS-CRP - 3.1±1.1. During a pandemic, messages from patients came in daily from 1 to 16.Their review and preparation of a response by a doctor per call took an average of 5 minutes; usually it took no more than 30 minutes to answer each day.Conclusion. The “ASpine” program for patients with axial spondyloarthritis during a difficult situation in the country caused by restrictive means of preventing COVID-19 provided real help as an alternative method of communication with the attending physician. In turn, the technology allows a rheumatologist to remotely monitor the health status of a large number of time expenditures (no more than 30 minutes per day for 71 patients).